PEREMPUAN DAN PERSPEKTIF SOSIAL DALAM NOVEL INDONESIA MUTAKHIR KARYA WANITA PENGARANG - - Sulaiman (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2010)
Lately, literary development is remarked by the appeareance of several women who declare themselves as writers. Through their works, they participate in enriching latest Indonesian literatures. They use women and their existency as central idea in each narration. In each narration, the women writers attempt to raise women’s dignities and status to be equal or even higher than men. The belief that men have more power and abilities than women is denied. To them, men and women have the same roles which depend on their existencies in their social life.